The impact of paternal age on cumulative assisted reproductive technology outcomes - Farabet, Clemence; Pirtea, Paul; Benammar, Achraf; De Ziegler, Dominique; Marchiori, Claire; Vallée, Alexandre; Ayoubi, Jean-Marc (Frontiers in Medicine, 2024)
ABSTRACT: Objective: To investigate the impact of paternal age on cumulative live birth rate in ART Design: Retrospective single center cohort study Patient(s): All female patients 18-43 years old, and males 18-60 years old who performed their first ART cycle between January 2018 and December 2020 were included. Intervention(s): N/A Main Outcome Measure(s): The primary outcome, cumulative live birth rate (cLBR), was estimated following fresh or frozen embryo transfers issued from an ART cycle. Secondary outcomes included: cumulative pregnancy rate (cPR), miscarriage rate. subgroups analyses were performed, as follows: males <45 and ≥ 45; female <35,35-38, and >38 years. Result(s): 2,358 couples were included. Male patients within both age groups had sperm quantity divided in 2 groups: normal and abnormal, that were found to be in significantly equal proportions. There was significantly less current smokers in the male group ≥45. cPR was 0.5301 in the group <45 and 0.3111 in the group ≥45, p < 0.001. Analysis according to the female age, in the female group > 38: cLBR rate was 0.26 for male <45 and 0.19 for male ≥45, p=0.061. Also, cPR was 0.34 in the male group <45 and 0.21 in the group ≥45, p< 0.001. In the female group 35-38 cLBR was 0.44 in the male group <45 and 0.3 in the group ≥45, p=0.031. cPR was 0.49 in the male group <45 and 0.34 in the group ≥45, p=0.036. Within the female group <35, we observed non-significant results. Miscarriage rate results weren’t significantly different for women ≤38. Conclusion: According to our result, male age 45 has a significant impact on cumulative ART outcomes.